Design of thin steel battens subject to pull-through failures. (July 2022) - Sivapathasundaram, Mayooran; Mahendran, Mahen; Myuran, Kathekeyan
Abstract: Localized pull-through failures of cold-formed steel roof battens have often been observed at the roof batten to purlin/rafter/truss screw connections during storms and cyclones. Recent research studies have therefore proposed improved design capacity equations by undertaking both experimental studies and finite element analyses. However, they have not investigated the effects of very thin steel roof and ceiling battens (<0.50 mm), safety lip features and purlin flexibility on the localized pull-through failures. Hence this study was aimed at investigating the effects of all such practical design issues and to assess the suitability of current design equations. For this purpose, a series of static and fatigue pull-through failure tests of roof and ceiling battens was undertaken under simulated static and cyclic wind uplift loads. This paper presents the details and results obtained from this study including suitable design recommendations. It has shown that the recently developed pull-through capacity equations can be used for very thin steel battens. Higher capacity reduction factors are recommended for use with these design equations for battens made of Australian cold-formed steels used in this study. The use of safety lip features did not affect the static pull-through capacities, but it improved the fatigue performance of roof battens. Finally, the suitability of using low strength steel battens instead of high strength steel battens was evaluated.